2015
DOI: 10.1111/mcn.12183
|View full text |Cite
|
Sign up to set email alerts
|

The effect of balanced protein energy supplementation in undernourished pregnant women and child physical growth in low‐ and middle‐income countries: a systematic review and meta‐analysis

Abstract: The beneficial effect of balanced protein energy supplementation during pregnancy on subsequent child growth is unclear and may depend upon the mother entering pregnancy adequately nourished or undernourished. Systematic reviews to-date have included studies from high-, middle-and low-income countries. However, the effect of balanced protein energy supplementation should not be generalised. This review assesses the effect of balanced protein energy supplementation in undernourished pregnant women from low-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 38 publications
0
58
1
Order By: Relevance
“…For instance, our observed association between SAM infants and maternal anthropometric deficit on univariate analysis is consistent with other evidence that maternal nutritional status has both short‐ and long‐term associations with infant health (Liu et al, ; Wrottesley, Lamper, & Pisa, ). That supplementing undernourished mothers might have also benefits for their infants is biologically plausible but needs more evidence (Stevens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our observed association between SAM infants and maternal anthropometric deficit on univariate analysis is consistent with other evidence that maternal nutritional status has both short‐ and long‐term associations with infant health (Liu et al, ; Wrottesley, Lamper, & Pisa, ). That supplementing undernourished mothers might have also benefits for their infants is biologically plausible but needs more evidence (Stevens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the consequences of maternal dietary protein intake on pregnancy outcomes, particularly SGA. Although a Cochrane review concluded that there is no justification for prescribing high-protein nutritional supplements to pregnant women (67), a more recent meta-analysis of studies from low-medium income countries found that balanced protein-energy supplementation of undernourished women significantly improved birthweight (68). Although the link between maternal protein malnutrition and hypertension in the offspring has been established (69), one study with Dutch women showed that protein intake-related acid load was not associated with HDPs, in protein-replete women (70).…”
Section: Nutrition and Blood Pressurementioning
confidence: 99%
“…Similarly, balanced protein energy supplementation programmes have shown promising effects on birth outcomes (e.g. Stevens et al, 2015) The role of nutrition in mediating the effects of P-IPV on the offspring should, we thus argue, be further explored as a number of gaps remain. It is unfortunate, for example, that in studies linking P-IPV to low birth weight (e.g., see Donovan et al, 2016 for a review), maternal nutrition has not been investigated as a mediator.…”
Section: Maternal Nutritionmentioning
confidence: 99%